Impairment of Coronary Flow Reserve Evaluated by Phase Contrast Cine‐Magnetic Resonance Imaging in Patients With Heart Failure With Preserved Ejection Fraction. Issue 2 (February 2016) - Kato, Shingo; Saito, Naka; Kirigaya, Hidekuni; Gyotoku, Daiki; Iinuma, Naoki; Kusakawa, Yuka; Iguchi, Kohei; Nakachi, Tatsuya; Fukui, Kazuki; Futaki, Masaaki; Iwasawa, Tae; Kimura, Kazuo; et al.
Abstract : Background: Phase contrast (PC) cine‐magnetic resonance imaging (MRI) of the coronary sinus allows for noninvasive evaluation of coronary flow reserve (CFR), which is an index of left ventricular microvascular function. The objective of this study was to investigate coronary flow reserve in patients with heart failure with preserved ejection fraction (HFpEF). Methods and Results: We studied 25 patients with HFpEF (mean and SD of age: 73±7 years), 13 with hypertensive left ventricular hypertrophy (LVH) (67±10 years), and 18 controls (65±15 years). Breath‐hold PC cine‐MRI images of the coronary sinus were obtained to assess blood flow at rest and during ATP infusion. CFR was calculated as coronary sinus blood flow during ATP infusion divided by coronary sinus blood flow at rest. Impairment of CFR was defined as CFR <2.5 according to a previous study. The majority (76%) of HFpEF patients had decreased CFR. CFR was significantly decreased in HFpEF patients in comparison to hypertensive LVH patients and control subjects (CFR: 2.21±0.55 in HFpEF vs 3.05±0.74 in hypertensive LVH, 3.83±0.73 in controls; P <0.001 by 1‐way ANOVA). According to multivariable linear regression analysis, CFR independently and significantly correlated with serum brain natriuretic peptide level (β=−68.0; 95% CI, −116.2 to −19.7; P =0.007). Conclusions: CFR was significantly lower in patients with HFpEF than in hypertensive LVH patients and controls. These results indicated that impairment of CFR might be a pathophysiological factor for HFpEF and might be related to HFpEF disease severity.